Answer

Verified

450.3k+ views

Hint: Try to use the following identities such as $\cos 2x=1-2{{\sin }^{2}}x,{{\sin }^{2}}x=2\sin x\cos x$ and lastly, $-\sqrt{{{a}^{2}}+{{b}^{2}}}\le a\sin \theta +b\cos \theta \le \sqrt{{{a}^{2}}+{{b}^{2}}}$ to get the desired results.

Complete step-by-step answer:

In the question given, the equation is

$\sin x\left( \sin x+\cos x \right)=k...........\left( i \right)$

Now, we will expand the equation (i), we will get;

$k={{\sin }^{2}}x+\sin x\cos x..............\left( ii \right)$

Now, we know the identity,

$\cos 2x=1-2{{\sin }^{2}}x$

Which can also be written as

$2{{\sin }^{2}}x=1-\cos 2x$

So, ${{\sin }^{2}}x=\dfrac{1-\cos 2x}{2}...........\left( iii \right)$

Now, we will use another identity;

$\sin 2x=2\sin x\cos x$

Which can also be formed as;

$\sin x\cos x=\dfrac{\sin 2x}{2}...........\left( iv \right)$

Now, substituting the results of equation (iii) and (iv) in equation (ii) we get;

$\begin{align}

& k=\dfrac{1}{2}-\dfrac{\cos 2x}{2}+\dfrac{\sin 2x}{2} \\

& \Rightarrow k=\dfrac{1}{2}+\dfrac{\sin 2x}{2}-\dfrac{\cos 2x}{2}.............\left( v \right) \\

\end{align}$

Now, we will use another identity which is;

$-\sqrt{{{a}^{2}}+{{b}^{2}}}\le a\sin \theta +b\cos \theta \le \sqrt{{{a}^{2}}+{{b}^{2}}}$

We can replace $\theta $ by $2x$ and $\dfrac{1}{2}$ in place of $a$ and $-\dfrac{1}{2}$ in place of $b$.

We get;

\[\Rightarrow -\sqrt{{{\left( \dfrac{1}{2} \right)}^{2}}+{{\left( -\dfrac{1}{2} \right)}^{2}}}\le \left( \dfrac{1}{2} \right)\sin \left( 2x \right)+\left( -\dfrac{1}{2} \right)\cos 2x\le \sqrt{{{\left( \dfrac{1}{2} \right)}^{2}}+{{\left( -\dfrac{1}{2} \right)}^{2}}}\]

Solving this, we get

\[\begin{align}

& \Rightarrow -\sqrt{\dfrac{1}{4}+\dfrac{1}{4}}\le \dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \sqrt{\dfrac{1}{4}+\dfrac{1}{4}} \\

& \Rightarrow -\dfrac{1}{\sqrt{2}}\le \dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \dfrac{1}{\sqrt{2}} \\

\end{align}\]

Now we will add $\dfrac{1}{2}$ to all the sides of inequality. We get;

$\dfrac{1}{2}-\dfrac{1}{\sqrt{2}}\le \dfrac{1}{2}+\dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \dfrac{1}{2}+\dfrac{1}{\sqrt{2}}$

Now, we substitute the whole value of $\left( \dfrac{1}{2}+\dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x \right)$ by $'k'$ from equation (v), we get

$\dfrac{1}{2}-\dfrac{1}{\sqrt{2}}\le k\le \dfrac{1}{2}+\dfrac{1}{\sqrt{2}}$

Taking the LCM, we get

$\dfrac{1-\sqrt{2}}{2}\le k\le \dfrac{1+\sqrt{2}}{2}$

So, the answer is option (d).

Note: In these type of questions student generally get confused while converting $\sin x\cos x$ and ${{\sin }^{2}}x$ in the terms of $\sin 2x\text{ and }\cos 2x$ respectively.

Students generally don’t expand the given equation and start substituting values of different identities as it is, that is directly in the equation $\sin x\left( \sin x+\cos x \right)=k$. In this way they will get confused and will get the wrong answer.

Complete step-by-step answer:

In the question given, the equation is

$\sin x\left( \sin x+\cos x \right)=k...........\left( i \right)$

Now, we will expand the equation (i), we will get;

$k={{\sin }^{2}}x+\sin x\cos x..............\left( ii \right)$

Now, we know the identity,

$\cos 2x=1-2{{\sin }^{2}}x$

Which can also be written as

$2{{\sin }^{2}}x=1-\cos 2x$

So, ${{\sin }^{2}}x=\dfrac{1-\cos 2x}{2}...........\left( iii \right)$

Now, we will use another identity;

$\sin 2x=2\sin x\cos x$

Which can also be formed as;

$\sin x\cos x=\dfrac{\sin 2x}{2}...........\left( iv \right)$

Now, substituting the results of equation (iii) and (iv) in equation (ii) we get;

$\begin{align}

& k=\dfrac{1}{2}-\dfrac{\cos 2x}{2}+\dfrac{\sin 2x}{2} \\

& \Rightarrow k=\dfrac{1}{2}+\dfrac{\sin 2x}{2}-\dfrac{\cos 2x}{2}.............\left( v \right) \\

\end{align}$

Now, we will use another identity which is;

$-\sqrt{{{a}^{2}}+{{b}^{2}}}\le a\sin \theta +b\cos \theta \le \sqrt{{{a}^{2}}+{{b}^{2}}}$

We can replace $\theta $ by $2x$ and $\dfrac{1}{2}$ in place of $a$ and $-\dfrac{1}{2}$ in place of $b$.

We get;

\[\Rightarrow -\sqrt{{{\left( \dfrac{1}{2} \right)}^{2}}+{{\left( -\dfrac{1}{2} \right)}^{2}}}\le \left( \dfrac{1}{2} \right)\sin \left( 2x \right)+\left( -\dfrac{1}{2} \right)\cos 2x\le \sqrt{{{\left( \dfrac{1}{2} \right)}^{2}}+{{\left( -\dfrac{1}{2} \right)}^{2}}}\]

Solving this, we get

\[\begin{align}

& \Rightarrow -\sqrt{\dfrac{1}{4}+\dfrac{1}{4}}\le \dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \sqrt{\dfrac{1}{4}+\dfrac{1}{4}} \\

& \Rightarrow -\dfrac{1}{\sqrt{2}}\le \dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \dfrac{1}{\sqrt{2}} \\

\end{align}\]

Now we will add $\dfrac{1}{2}$ to all the sides of inequality. We get;

$\dfrac{1}{2}-\dfrac{1}{\sqrt{2}}\le \dfrac{1}{2}+\dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x\le \dfrac{1}{2}+\dfrac{1}{\sqrt{2}}$

Now, we substitute the whole value of $\left( \dfrac{1}{2}+\dfrac{1}{2}\sin 2x-\dfrac{1}{2}\cos 2x \right)$ by $'k'$ from equation (v), we get

$\dfrac{1}{2}-\dfrac{1}{\sqrt{2}}\le k\le \dfrac{1}{2}+\dfrac{1}{\sqrt{2}}$

Taking the LCM, we get

$\dfrac{1-\sqrt{2}}{2}\le k\le \dfrac{1+\sqrt{2}}{2}$

So, the answer is option (d).

Note: In these type of questions student generally get confused while converting $\sin x\cos x$ and ${{\sin }^{2}}x$ in the terms of $\sin 2x\text{ and }\cos 2x$ respectively.

Students generally don’t expand the given equation and start substituting values of different identities as it is, that is directly in the equation $\sin x\left( \sin x+\cos x \right)=k$. In this way they will get confused and will get the wrong answer.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Give 10 examples for herbs , shrubs , climbers , creepers

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE